Penerapan Aplikasi Akuntansi Berbasis Web SI APIK dalam Penyusunan Laporan Keuangan pada UMKM Rumah Makan di Kota Manado - Syaefudin, Fanesa I. M.; Putong, Ivonne H.; Wenas, Jacqualine Greety; Wangarry, Andreas Randy (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
UMKM (Micro, Small and Medium Enterprises) have a very important role in the Indonesian economy, including in the city of Manado. One of the main challenges faced by UMKM players is limited knowledge in preparing good and correct financial reports. This often causes difficulties in business management, decision making, and access to funding sources. Therefore, outreach and assistance activities in preparing financial reports are very important. This research aims to provide understanding and skills in preparing financial reports to UMKM, especially Brave Cafe’s owner in Manado City. Socialization activities are carried out with an approach that is easy to understand and relevant to their business needs. Apart from that, direct assistance is provided to business owners to prepare financial reports based on SAK EMKM for UMKM. The results of this activity show that there is an increase in understanding of UMKM players in preparing more systematic and accurate financial reports. Banjer Fruit Kios, which previously had difficulty managing financial reports, can now create reports that help monitor the financial condition of their business. This assistance also has a positive impact in improving business performance and opens up opportunities to obtain financing assistance from financial institutions.